Reforming Tax Expenditures in Italy : What, Why, and How? - Tyson, Justin (Washington, D.C. : International Monetary Fund, 2014)
The IMF has advised country authorities to roll back tax expenditures as a way to support fiscal consolidation efforts-urging them to evaluate tax expenditures according to clear criteria, and assessing their impact on public finances, economic efficiency, equity, and administrative and compliance costs. This paper analyzes tax expenditures in Italy, considering the extent to which tax expenditures can be considered part of an optimal tax system and possible reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet